2013
DOI: 10.1155/2013/636927
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Cancer in Diabetes: The Effect of Metformin

Abstract: Cancer is the second cause of death. Association of diabetes as a growing and costly disease with cancer is a major health concern. Meanwhile, preexisting diabetes is associated with an increased risk of all-cause and cancer-specific mortalities. Presence of diabetes related comorbidities, poorer response to cancer treatment, and excess mortality related to diabetes are among the most important explanations. Although diabetes appear to be a risk factor for cancer and is associated with the mortality risk in ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
50
0
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 86 publications
(72 reference statements)
0
50
0
4
Order By: Relevance
“…Metformin reduces adenosine triphosphate (ATP) production, resulting in an increased AMP:ATP ratio, which leads to activation of the liver kinase B1 (LKB1)-AMPK signaling pathway (2,(21)(22)(23) (2,(24)(25)(26). Additional studies have suggested that metformin may inhibit carcinogenesis and/or cancer cell growth via diverse pathways (15,(27)(28)(29). Phosphorylation of the AMPK catalytic subunit occurs in the presence of LKB1, and is facilitated by AMP.…”
Section: Metformin Mechanism Of Actionmentioning
confidence: 99%
See 4 more Smart Citations
“…Metformin reduces adenosine triphosphate (ATP) production, resulting in an increased AMP:ATP ratio, which leads to activation of the liver kinase B1 (LKB1)-AMPK signaling pathway (2,(21)(22)(23) (2,(24)(25)(26). Additional studies have suggested that metformin may inhibit carcinogenesis and/or cancer cell growth via diverse pathways (15,(27)(28)(29). Phosphorylation of the AMPK catalytic subunit occurs in the presence of LKB1, and is facilitated by AMP.…”
Section: Metformin Mechanism Of Actionmentioning
confidence: 99%
“…1 outlines the potential anticancerogenic effects of metformin. Metformin activates AMPK in the liver and skeletal muscles, thereby reducing gluconeogenesis in the liver and enhancing glucose uptake by the peripheral tissues, resulting in lower blood glucose and insulin levels (2,15,16). Insulin has been found to exert mitogenic activity and thus may, theoretically, have a promotional effect on the growth of tumor cells.…”
Section: Metformin Mechanism Of Actionmentioning
confidence: 99%
See 3 more Smart Citations